PERFORMA GENERATOR HHO DALAM SISTEM BI-FUEL PADA SEPEDA MOTOR SEBAGAI BAHAN BAKAR ALTERNATIF - Ika Kusuma Nugraheni; Anggun Angkasa; Abdul Rahman Rifa’i (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
The increasing of vehicle uses will make the increasing in fuels consumption. In the other hand, the reserves of fossil fuels as a fuel in vehicles are always decreasing. In order to anticipate the lack of fossil fuels, there is some alternatives energy that has to substitute the fossil fuels. One of the alternative energy is HHO Gas. HHO gas is a gas that was produced by the electrolysis of water. Water as an abundant material in earth can be an alternative energy that replace or substitute fossil fuel. In this research, HHO gas will be used as a supplement in fuels. So the vehicles use two fuels (bi-fuel. )The aim of this research is to analyze the performance of uses HHO gas in vehicles. The HHO gas will be produced by different water, such as aquadest, land water, sea water. The performance analysis was focused in the fuel consumption and the efficiency of thermal engine oil. The analysis result shows that the addicted HHO gas can make the efficiency of fuel consumption better. The highest efficiency fuel consumption is in the fuel with HHO gas from aquadest (19.95%). But the best efficiency in thermal engine oil is in HHO gas from sea water (0.84 oC). Keywords: HHO, performance, engine, bifuel